The Effect of Service Quality, Brand Trust, and Promotion on Customer Loyalty Through Customer Satisfaction at Shopee Indonesia - Fathin Aliaa Hamdi; Syafiqah Dewi Ramadhani; Dr. Osly Usman, M.Bus Syst (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
The purpose of this study is to examine how customer service quality, brand trust, and promotion affect customer loyalty through customer satisfaction. Meanwhile, to analyze the relationship between variables, using partial least squares (PLS). The composite dependability value of the internal consistency test met the parameters. Every indicator variable statement has satisfied the requirements for validity and reliability based on the test results. The hypothesis test with SmartPLS 4.0 show that service quality has an positive indirect effect on customer loyalty, brand trust had a positive and significant indirect effect on customer loyalty, promotion had a positive and significant indirect effect on customer loyalty. The influence of Service Quality on Customer Loyalty through Customer Satisfaction has a postive and significant indirect relationship. The influence of Brand Trust on Customer Loyalty through Customer Satisfaction has a postive and significant indirect relationship. And there is a postive and significant indirect relationship of Brand Trust on Customer Loyalty through Customer Satisfaction.